Spontaneous Formation of Interwoven Porous Channels in Hard-Wood-Based Hard-Carbon for High-Performance Anodes in Potassium-Ion Batteries. Issue 9 (13th July 2017) - Prabakar, S. J. Richard; Han, Su Cheol; Park, Chunguk; Bhairuba, Ikhe Amol; Reece, Michael J.; Sohn, Kee-Sun; Pyo, Myoungho
Abstract : For the first time we report that hard-wood (oak) can spontaneously create interconnected channels of μm to nm in diameter during carbonization at an optimized temperature (1100°C). These microstructural features have never been found in other hard-carbons without the use of additives. When compared with sucrose-based hard-carbon (SHC), oak-based hard-carbon (OHC) shows much higher charge-storage capability (ca. 223 vs. 112 mAh·g −1 at 20 mA·g −1 ) and excellent stability (fading rate of 0.04 vs. 0.08%·cycle −1 ) as an anode in potassium-ion batteries. The high performance of OHC mainly results from interwoven nanoporous channels, which lead to facile charge transfer and fast K + -diffusion.